2019
DOI: 10.1021/acsearthspacechem.9b00194
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth of Smectite: A Study Based on the Change in Crystal Chemistry and Morphology of Saponites with Synthesis Time

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 61 publications
5
26
0
Order By: Relevance
“…The S of the bands is proportional to the concentration of absorbing centers of the given OH types, assuming that the absorption coefficients are constant for all metal OH stretching vibration bands (e.g., Slonimskaya et al, 1986;Petit et al, 2004;Madejová et al, 2017). The decomposition of the spectral envelop into bands was undertaken by the Peakfit software package, using four Gauss-Lorentz cross-product (Zhang et al, 2020). Correspondingly, the dissolution extent (i.e., the dissolution ratio of precursors) can be estimated by…”
Section: Analysis Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The S of the bands is proportional to the concentration of absorbing centers of the given OH types, assuming that the absorption coefficients are constant for all metal OH stretching vibration bands (e.g., Slonimskaya et al, 1986;Petit et al, 2004;Madejová et al, 2017). The decomposition of the spectral envelop into bands was undertaken by the Peakfit software package, using four Gauss-Lorentz cross-product (Zhang et al, 2020). Correspondingly, the dissolution extent (i.e., the dissolution ratio of precursors) can be estimated by…”
Section: Analysis Methodsmentioning
confidence: 99%
“…These processes result in variations in crystal-chemistry and morphology of smectite, due to physicochemical condition changes that frequently occur in natural systems (Eberl, 1984;Merriman, 2005;Galán and Ferrell, 2013). Previous studies have reported that smectites evolve from poorly crystalline precursors in various environments (Zhou and Fyfe, 1989;Banfield and Eqqleton, 1990;Kawano and Tomita, 1992;Christidis, 2001; Christidis and Huff, 2009;Baldermann et al, 2015;Cuadros et al, 2017;Zhang et al, 2020), which is important for This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations